PENGARUH PEMBERIAN KOMPOS ELA SAGU DAN PUPUK ABG BUNGA-BUAH TERHADAP P-TERSEDIA, SERAPAN-P, SERTA PERTUMBUHAN TANAMAN JAGUNG (Zea mays L.) PADA INCEPTISOLS - E. Kaya (BUANA SAINS, 2012)
The aim of this study was to determine the effect of compost application and ABG fertilizer (fruit and flower) on soil pH, availability and absorption of phosphorus, and growth of maize (Zea mays L.) in an Inceptisol. The study was conducted at a green house of Agricultrural Faculty of Pattimura University by employing a completely randomized block design with three repelicates. The treatments consisted of two factors: I sagu compost (0, 25, and 50 g/pot) and ABG fertilizer (0, 1, 2 mL/L of water). The results showed that application of sagu compost and ABG fertilizer separately increased soil pH, availability of phosphorus, absorption of P and diameter size of maize. Mixing application of sagu compost and ABG fertilizer increased plant hight of maize from 54,23 cm to 104,57 cm